A field evaluation of an isothermal DNA amplification assay for the detection of Theileria annulata infection in cattle. (February 2017) - Gomes, Jacinto; Santos, Marcos; Amaro, Ana; Pereira da Fonseca, Isabel; Santos-Gomes, Gabriela; Inácio, João
Abstract: A loop-mediated isothermal amplification (LAMP) assay was evaluated for the detection of Theileria annulata infection in cattle. The results were compared with a real-time PCR used for the quantification of T. annulata parasitaemia. One hundred bovine blood samples from 16 cattle farms were tested with LAMP and real-time PCR, with T. annulata DNA being detected in 66% and 67% of the samples, respectively. The results showed that the LAMP assay detects a parasitaemia as low as 0.00025%, indicating a high analytical sensitivity of LAMP for clinical diagnosis of bovine theileriosis. Highlights: A LAMP assay for specific detection of Theileria annulata in cattle was evaluated in a field trial. A detection of a 0.00025% parasitaemia was achieved. The assay is useful for simple and rapid detection of T. annulata from clinical samples.